Navigating difficult waters : learning for career and labour market transitions - (:unkn) unknown (Publications Office of the European Union, 2014)
"This report analyses how learning supports labour market transitions and career changes of adult workers across five countries (Denmark, Germany, Spain, France and Italy). To make the most of career and labour market opportunities, individuals have to rely on their own resources and their agency but also know how to navigate the institutional context. To make successful labour market transitions, individuals need to have a sense of direction, they need to learn about opportunities, and they need to learn skills. Education and training has a special role in supporting adult workers in their careers, providing them with the competences, qualifications and, in some cases, with the self-confidence needed for successful transition. Guidance services tailored to individual needs can help individuals find appropriate career trajectories in their search for suitable job opportunities, and can foster relational, emotional, cognitive and practical learning." (Publisher, BIBB-Doku)
Keywords: G 1.3.3 Bildungs- & Erwerbsbiografien; L 5.1 Berufswahlberatung; L 5.3 Bildungs(gang)beratung; G 2.2.4 Lebensbegleitendes & lebenslanges Lernen; I 2.1 Deutschland; I 2.2.1 Westeuropa; Berufsverlauf; Qualifikationsverwertung; Berufserfolg; Einflussfaktor; Berufswegplanung; Bildungsberatung; Lebenslanges Lernen; Internationaler Vergleich; Bundesrepublik Deutschland; Dänemark; Frankreich; Italien; Spanien